PUNCHING SHEAR STRENGTHS OF HYBRID REINFORCED CONCRETE FLAT PLATE SLABS - Suha Rasheed Abass; Haitham Jameel Abd (Journal of Engineering and Sustainable Development, 2018)
This study is conducted to test experimentally the punching shear of reinforced concrete flat plate slabs made with hybrid concrete (two types of concrete in two layers in specimens. Twelve test slab with ( 450×450×50 ) mm dimension The tested slabs have been. divided into four groups, each of which consisted of three slab specimens identical in size and shape but different in concrete type and steel bar reinforcement. All slabs are simply supported along the all edges and subjected to single point load applied at the center of gravity of each slab.Experimental results show that the use of hybrid concrete and high strength concrete improves the punching shear resistance and allows higher forces to be transferred through the slab-column connection. For slab specimen which fully cast using high strength concrete, the ultimate shear capacity increased by (40%) in comparison with the normal concrete slabs. While, for slab specimens cast using with hybrid concrete the ultimate shear capacity increased by (5%-45%) in comparison with the normal concrete slabs.This experimental results revealed that the ultimate load capacity increase with the addition of super plasticizers to the mix of concrete.